Reactivation Strategies and Development of Tuban Station as a Heritage Building - Ibrahim, Satria Bhirawa Nur; Aghastya, Adya; Riyanta, Wawan (Nusantara Publisher, 2025)
Tuban Station is located in Tuban Regency. According to the National Railway Master Plan of 2018 and Presidential Regulation No. 80 of 2019, the Jombang – Babat – Tuban route is included in the reactivation plan aimed at promoting equitable development and accelerating growth in the Gerbang Kertosusila region. This reactivation project will involve the renovation of Tuban Station, a cultural heritage building over 50 years old, to serve as a boarding and alighting point for passengers traveling through Tuban. Tuban Station is one of the few remaining stations along the Jombang – Babat – Tuban route. Currently, the station is being utilized by the local community as a culinary center. The objective of this study is to design the heritage building of Tuban Station in accordance with its designated class and the layout requirements specified in Minister of Transportation Regulation No. 33 of 2011 and Ministerial Regulation No. 29 of 2011, while preserving its original historical appearance. The design process for Tuban Station follows the Station Standardization Book of 2012, employing AutoCAD for 2D designs and Google SketchUp for 3D modeling. The outcome of this research includes the working drawings and 3D design of Tuban Station, fully complying with the classification outlined in the Station Standardization Book of 2012.